Pengaruh Pengetahuan Investasi, Motivasi dan Modal Minimal Investasi terhadap Minat Investasi Mahasiswa di Pasar Modal (Studi Kasus Mahasiswa ITB AAS) - Fadia Rifqi Sutarno Putri; Suprihati Suprihati; Maya Widyana Dewi (Lembaga Yasin AlSys, 2026)
Although access to the capital market has become increasingly convenient, students’ investment interest remains relatively low, while previous studies on the effects of investment knowledge, motivation, and minimum investment capital on investment interest have produced inconsistent findings. This study aimed to analyze the effects of investment knowledge, motivation, and minimum investment capital on students’ interest in investing in the capital market at Institut Teknologi Bisnis AAS Indonesia. The study employed a quantitative approach involving 89 respondents selected through proportional random sampling. Data were collected using a questionnaire and analyzed through partial hypothesis testing. The results showed that investment knowledge had no significant effect on students’ investment interest, with a significance value of 0.912 > 0.05 and a t-value of −0.111 < the critical t-value of 1.988. In contrast, motivation had a positive and significant effect on investment interest, with a significance value of 0.000 < 0.05 and a t-value of 6.725 > the critical t-value of 1.988. Minimum investment capital also had a positive and significant effect on students’ investment interest, with a significance value of 0.000 < 0.05 and a t-value of 7.888 > the critical t-value of 1.988. These findings confirm that motivation and capital affordability are the main factors encouraging students’ interest in investing, whereas investment knowledge that remains theoretical has not significantly increased their investment interest. This study implies the need to strengthen more practical investment education in higher education institutions and to provide programs that can enhance students’ motivation and practical experience in investing in the capital market.